3D antenna for wireless power transmission aperture coupled microstrip antenna with dielectric lens - Dias, Gonçalo (2019)
Nowadays 3D printers are useful for the development and rapid prototyping of dielectric structures for radiation manipulation and support of antennas. This is possible since the materials used in this machines are essentially dielectric. These can be used as radiating elements (dielectric resonators), as radiation handlers (lenses) or as a supporting base for applying conductive material to radiation (substrates). In this paper we explore 3D printing technology to develop a lens antenna for wireless power transfer operating at 20 GHz. The design, simulation and measurement of an aperture coupled microstrip antenna with dielectric lens is presented and discussed. The lens is used to focus the beam of lower gain feed antenna to produce a highly directive pattern with low side lobe.